A study of the learning experience from an emerging technology integrated curriculum - Wang, Pi-Hsia; Chiang, Shan-Ting; Tseng, Shu-Feng; Wu, Pai-Lu (International Journal of Scientific Research and Management (IJSRM), 2017)
This study aims to explore the learning effect of emerging technology integration in a senior high schoolcurriculum as implemented by the High Scope Project of the Ministry of Science and Technology, R.O.C.Through senior high school teachers’ inquiry instruction and interaction with students, it explores students’learning experience in an emerging technology integrated curriculum and further probes into subjects’perception and effect of the experience. The research questions are: (1) What are the subjects’ pastexperience with emerging technology? (2) What is the subjects’ feedback from participating in an emergingtechnology integrated curriculum practiced by teachers? (3) What is students’ personal reflection afterparticipating in an emerging technology integrated curriculum? This study adopts qualitative research ofin-depth interviews, and the subjects are 6 students in one senior high school in southern Taiwan. Since thesubjects are senior high school students who participate in an emerging technology integrated curriculumand the recorded interviews and observations are based on their agreement, this study practices purposivesampling. The research tool is the researcher’s self-designed interview outline. The study is based onmultiple sources such as in-depth interviews, observations, and feedback. The main findings of this study areas follows: 1) senior high school students’ past behavior with emerging technology is rare; 2) teachersproposed practice courses that include immediate feedback and interaction, and these courses are the mostpopular with students. Teachers’ questions and encouragement and students’ problem-solving process resultin students having a positive learning effect; 3) with experience from participating in competitions, studentsdevelop personal reflection and confidence. External praises lead to the construction of personal positiveself-concept; 4) important self-reflection includes acquisition of new knowledge, passion in attempts,demand for a great amount of originality and ideas, etc.